The Risks to Investment Decisions: Can Financial Knowledge and Investor’s Experience be Moderate? - Hirdinis M. (Studies in Business and Economics)
This research is intended to determine the risk of investment-decisions moderated by investors’ knowledge and experience on the Indonesian Stock Exchange (IDX). The object of this research is investors who invest on the IDX with an unknown population, and the number of samples in this research is 210 investors. Data analysis in this research uses an alternative method of structural equation modeling (SEM), namely Smart-PLS 3. The results of the research show that risk aversion and risk perception have a significant positive effect on investment decisions. Financial knowledge cannot moderate the influence of risk aversion on investment decisions. Investment experience can moderate the influence of risk perception on investment decisions. So investment experience can strengthen the significant influence of risk perception on investment decisions. Investors of productive age who are educated with good investment experience are able to show a careful attitude in managing risk perceptions regarding investment decisions.